Física no ensino médio e estudantes trabalhadores: buscando relações entre significado e sentido para a aprendizagem. - Toti, Frederico Augusto (2007)
According to the report of the Inter-American Bank of Development (BID) of 2000 and data from the National Secondary Education Examination (ENEM) of 2003, it is a necessity for the majority of Brazilian students who attend secondary school to conciliate studies and work. This reality can be a challenge for these students regarding their attendance and progress in school but on the other hand it can provide new conceptual horizons and perspectives that are favourable for the fusion of knowledge that is originated from the work practice and systematised knowledge learned in school. This fusion can mean new learning opportunities both in school and in the workplace, better progress in school and it can also show us possible ways of overcoming the dichotomy between theory and practice. Considering these potentialities in the face of the necessity of development of contents which are more linked to the reality of the Physics teaching, this research tried to relate fragments of knowledge in Physics which are present in the professional activities of the students to the knowledge in Physics which are typically addressed in secondary education. In order to do the research, a questionnaire was devised and it offered us a distribution of the students who work and study at secondary schools at night in Araraquara SP. Later these worker students were interviewed and their workplaces visited with the purpose of identifying fragments of knowledge of Physics present in their work activities and the personal sense students attribute to the school knowledge. A classroom research was also done in order to evaluate the students receptivity to an approach of Physics that take into consideration common elements from their work activities. The contribution of cultural-historical psychology, in particular the Cultural-Historical Activity Theory (LEONTIEV, 1978a) made possible an analysis that take into account the psychological elements that are involved in the human activities which gives grounds for the importance of creating conditions for the students to relate the personal purpose they attribute to the scientific knowledge learned at school and its social meaning. The results suggest that connexions between the Physics knowledge present in the students professional activities and that taught in school have the potential for the creation of new learning needs and this way worker students may attribute new personal sense to the learning of Physics.